On the order of convolution consistence of certain classes of harmonic functions with varying arguments - SĂLĂGEAN, Grigore Ștefan; PÁLL-SZABÓ, Ágnes Orsolya (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
Making use of a modified Hadamard product or convolution of harmonic functions with varying arguments, combined with an integral operator, we study when these functions belong to a given class. Following an idea of U. Bednarz and J. Sokol we define the order of convolution consistence of three classes of functions and determine it for certain classes of harmonic functions with varying arguments defined using a convolution operator. Mathematics Subject Classification (2010): 30C45, 30C50. Received 29 June 2021; Accepted 14 July 2021.